Mitigation of reactive metabolite formation for a series of 3-amino-2-pyridone inhibitors of Bruton's tyrosine kinase (BTK). Issue 3 (1st February 2017) - Lou, Yan; Lopez, Francisco; Jiang, Yongying; Han, Xiaochun; Brotherton, Chris; Billedeau, Roland; Gabriel, Steve; Gleason, Shelly; Goldstein, David M.; Hilgenkamp, Ramona; Kocer, Buelent; Orzechowski, Lucja; et al.
Graphical abstract: Abstract: Reactive metabolites have been putatively linked to many adverse drug reactions including idiosyncratic toxicities for a number of drugs with black box warnings or withdrawn from the market. Therefore, it is desirable to minimize the risk of reactive metabolite formation for lead molecules in optimization, in particular for non-life threatening chronic disease, to maximize benefit to risk ratio. This article describes our effort in addressing reactive metabolite issues for a series of 3-amino-2-pyridone inhibitors of BTK, e.g. compound1 has a value of 459 pmol/mg protein in the microsomal covalent binding assay. Parallel approaches were taken to successfully resolve the issues: establishment of a predictive screening assay with correlation association of covalent binding assay, identification of the origin of reactive metabolite formation using MS/MS analysis of HLM as well as isolation and characterization of GSH adducts. This ultimately led to the discovery of compound7 (RN941) with significantly reduced covalent binding of 26 pmol/mg protein.